Tagger Voting Improves Morphosyntactic Tagging Accuracy on Croatian Texts - Agić, Željko (Array, 2010)
We present results of an experiment dealing with combining outputs of five part-ofspeech taggers via tagger voting in order to improve the overall accuracy of morphosyntactic tagging of Croatian texts using a subset of the Multext-East v3 tagset. The increase in accuracy over the best- performing single tagger is shown to exist, but not to be statistically significant. We discuss the performance of the five single taggers, the overlaps between tagger pairs, the reduced tagset and the voting scheme, along with scores for five meaningful tagger combinations in the voting scheme and future work plans.